Greater motor unit discharge rate during rapid contractions in chronically strength-trained individuals - Škarabot, Jakob; Casolo, Andrea; Balshaw, Thomas G.; Maeo, Sumiaki; Lanza, Marcel Bahia; Holobar, Aleš; Farina, Dario; Folland, Jonathan P.; Del Vecchio, Alessandro (Journal of Neurophysiology, 2024)
Though similar motor unit (MU) discharge properties have been observed during slow sustained contractions between chronically strength-trained (ST) and untrained (UT) individuals, it is currently unknown whether differences between these groups exist for when maximal in vivo MU discharge rate is assessed during rapid, maximal rate of force development (RFD) contractions. Therefore, we compared MU discharge characteristics and RFD during rapid contractions in chronic ST and UT individuals. The investigations were performed in two independent cohorts of chronically ST men, with trained elbow flexors (experiment 1, n ¼ 13, 6 ± 4 yr of training experience) or knee extensors (experiment 2, n ¼ 11, 9 ± 4 yr of experience), and compared with those of UT (n ¼ 12 and n ¼ 10, respectively). ST individuals had greater absolute elbow flexion and knee extension RFD throughout the first 150 ms of rapid contractions compared with UT, but this difference was absent for relative RFD. ST exhibited higher initial MU discharge rate in both biceps brachii (74 [68, 80] vs. 56 [50, 63] pulses per second (pps), P < 0.0001) and vastus lateralis (102 [90, 115] vs. 76 [63, 90] pps, P ¼ 0.0025) and a greater average number of MU discharges per second in both trained muscles in the early phase of rapid contractions. We provide novel evidence for a higher maximal MU discharge rate in strength-trained individuals. Interestingly, despite the augmented output of the spinal cord, no differences in relative RFD were observed, which suggests either greater maximal force enhancement of ST compared with UT and/or slowing of the intrinsic contractile properties by prolonged strength training.
CRIS-Team Scopus Importer:2025-02-04
Keywords: decomposition; motoneuron; resistance training